Fluoroscopy-Assisted Percutaneous Endoscopic Gastrostomy (F-PEG)—Single-Center Experience and Outcome - Balekuduru, Avinash Bhat; Bongu, Shruti Sagar; Mandalapu, Narendra Babu; Ramachandraiah, Gajendra; Khemka, Vinit Kumar; Subbaraj, Satyaprakash Bonthala (Journal of Digestive Endoscopy, 2020)
Background Gastrointestinal route is considered for feeding in subjects who are unable to swallow, either as a temporary or permanent option. Percutaneous endoscopic gastrostomy (PEG) is the preferred mode for long-term enteral nutrition. The aim was to study the outcome of protocol-based PEG placement in a tertiary medical center.Materials and Methods All the patients who underwent PEG placement between January 2017 and December 2019 were included in the retrospective study. Study variables were entered into a uniform structured proforma. The procedure was done by two people using Ponsky-Gauderer pull-technique. Fluoroscopy guidance was considered for placement in special situations. Post-procedure, all the patients were regularly followed as per protocol to evaluate for adverse events.Results One hundred and eighteen patients with placement of PEG were included in the study. The mean age of the patients was 49.6 ± 7 years with 67.8% males. The most common indication of PEG was inability to swallow associated with head injury (43, 36.4%), followed by carcinoma esophagus (35, 29.8%) and stroke (24, 20.3%). Fluoroscopy was useful in 38 (32%) for PEG site identification. Tube dislodgement (16, 13.5%) and aspiration pneumonia (20, 16.9%) were the common adverse events. Age more than 60 years and dysphagia in neurologic disorders accounted for more than 60% of adverse events. Forty-nine (42%) of the PEG patients expired due to either primary illness or due to sepsis after a median time of 139 days (range: 32–288 days). There was no difference in the survival in patients with or without PEG-related complications (p = 0. 74).Conclusions Fluoroscopy assistance helps in accurate PEG placement in one third. Age > 60 years and dysphagia in neurologic disorders were independent risk factors associated with PEG tube complications.
Keywords: percutaneous endoscopic gastrostomy; fluoroscopy; complications; F-PEG